Decision Support System for Aren Sugar Aid Using SMART Method - anas anas; Rozalina Amran; Wakhid Yunendar (Journal of System and Computer Engineering, 2025)
Sugar palm (Arenga pinnata Merr) is a type of palm plant that is widely found in Indonesia. This plant is able to produce sap liquid from its cut flower bunches. Chemically, sugar palm sap contains 87.2% water, 12.7% carbohydrates, 0.24% ash, 0.2% protein, and 0.02% fat. Simple Multi Attribute Rating Technique is a multi-attribute decision-making method used to assist decision makers in determining several alternative choices. Each alternative is arranged based on a number of attributes, where each attribute has a certain value that is assessed on a certain scale. In addition, each attribute is given a weight that indicates its level of importance compared to other attributes. The application of a Decision Support System with this method can produce more effective, fast, and accurate decisions in the initial selection process for recipients of palm sugar production assistance. The reliability of this system is proven through testing using the White Box Testing and Basis Path Testing methods, which produce a V(G) value of 9.